ADULT EDUCATION REFORMS AND NATIONAL DEVELOPMENT IN NIGERIA - Ugwu , Chinwe U. (Journal of Continuing and Development Education, 2023)
Adult education programme as a tool for development in Nigeria has been neglected by the government in her developmental programmes. This paper examined the importance of adult education in the National Development programmes in Nigeria, Using the various programmes and the policy guideline provided by the National policy on education, adult education will reform a lot in the National development plan. Most of the agencies should study the various polices and streamline it to favour adult education and avoid the multiplication of the agencies without achieving its goals to meet the target of the sustainable development goals. It has been recommended that for adult education to be reformed, there must be an improvement in the perception of Adult Education at all levels of the government and the society at large.